PENGARUH PIJAT OKSITOSIN TERHADAP PENINGKATAN PRODUKSI ASI PADA IBU POST PARTUM DI RSIA MURNI TEGUH ROSIVA MEDAN - Rosalin Novalina Sipayung; Mhd. Taufik Daniel Hasibuan (Indonesian Trust Nursing Journal, 2026)
Breast milk is the best food for babies, containing complete nutrition and easily digested by the baby's stomach. However, some postpartum mothers cannot provide breast milk to their babies, one of the causes is due to low or irregular breast milk production. Oxytocin massage is thought to increase breast milk production in postpartum mothers. The objective of this study is to determine the Effect of Oxytocin Massage on Increasing Breast Milk Production in Postpartum Mothers. This study method is a quantitative Quasi Experiment study with a one group pre-test-post-test design. The study was conducted at RSIA Murni Teguh Rosiva Medan. The population was 29 people with a total sampling technique. The analysis was carried out univariately and bivariately using the Paired Sample T-Test. This study showed that before oxytocin massage was performed on postpartum mothers (pretest), the majority of mothers' breast milk production was in the poor category (<22 ml) (65.5%) with an average of 20.41±3.822. After oxytocin massage (posttest), mothers' breast milk production was in the very good category (>27 ml) (55.2%) with an average of 29.76±4.111. Oxytocin massage had a significant effect on increasing breast milk production in postpartum mothers, obtained p-value = 0.000 <0.05. It is concluded that there was a difference in breast milk production in postpartum mothers before and after oxytocin massage. It is recommended that further researchers conduct research using other techniques such as acupressure techniques, consumption of katuk leaves, and others.